Electrochemical studies of Fe(CN)6 4-/Fe(CN)6 3on gold ultramicroelectrodes varying the concentrations of KF as supporting electrolyte - Menolasina, Sabino (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
Gold disk ultramicroelectrodes of 10 Âµm diameter were fabricated using gold wires. These ultramicroelectrodes were characterized by electrochernical measurements and scanning electron microscopy (SEM). Electrochemical behavior of the hexacyano ferrate couple using gold ultramicroelectrodes (10 Âµm diameter) was investigated in a range of different concentrations of KF as supporting electrolyte. The steady state response at a gold ultramicrodisc at different concentrations of hexacyanoferrate couple with high concentrations of electrolyte was utilised to determine the diffusion coefficients of both electroactive species. Voltammetric experiments shown, that the oxidation and reduction of this couple is affected by the concentration of the supporting electrolyte. Theoretical Tafel plots were calculated considering double layer effects and comparisons with the experimental results indicated that determination of the heterogeneous rate constants for the free (unpaired) anions species seems to be imposible. Even at lower concentrations and after correction for double layer effects, the reaction is still dominated by ion pair effects.